The story of stuff : how our obsession with stuff is trashing the planet, our communities, and our health--and a vision for change - Leonard, Annie; Conrad, Ariane (New York : Free Press, 2010)
The director of The Story of Stuff Project tracks the life of the'stuff' we use every day, transforming how we think about our patterns of consumption. This book is based on the author's 2007 internet film,'The Story of stuff.''With just 5 percent of the world's population, [the U.S.] is consuming 30 percent of the world's resources and creating 30 percent of the world's waste.' -- Dust jacket.
A word about words -- Extraction -- Production -- Distribution -- Consumption -- Disposal -- Writing the new story -- Examples of promising policies, reforms, and laws -- Recommended individual actions -- Sample letter to PVC retailers, manufacturers, and lobbyists -- How we made this book.
Includes bibliographical references (p. 269-302) and index.
Keywords: Acquisitiveness -- Moral and ethical aspects; Consumption (Economics) -- Moral and ethical aspects; Consumption (Economics) -- Environmental aspects; Consumption (Economics) -- Social aspects; Personal belongings; Material culture; Sustainable development